Dry separation using a fluidized Sink-Hole. (October 2018) - Kumar, D.; Iveson, S.M.; Galvin, K.P.
Highlights: Vibrated air-fluidised bed of dense medium (sand particles). Screen with large Sink-Hole (compared to aperture) placed at bed surface. Robust density-based batch separation of heavy mineral fines (typically 1–10 mm). Cut point ( D 50) greater than the medium density was achieved. Potential to shift cut-point by varying sand mass (bed height) and air flow rate. Abstract: Dry separation of heavy-mineral particles such as iron ore in the nominal size range of 1–10 mm is a significant challenge. This paper reports the findings of dry separation experiments conducted under batch conditions using a novel device referred to as the Sink-Hole fluidizer. The device utilizes a fluidized bed, with vibration applied as an additional energy source to disrupt the tendency of the excess air to pass through as bubbles. The fluidized bed is covered by a fine mesh containing holes with a nominal 1 mm square aperture. A much larger hole located at the centre acts as the "Sink-Hole". When the system is fluidized the media expands, passing up through the Sink-Hole, spilling onto the adjacent mesh, and sifting back into the lower bed. For this work nominal 200 μm sand was used as the bed media. Tracer particles of density 2.4 to 4.8 RD, covering the size range from 2.0 to 8.0 mm, were added onto the mesh. The vibration caused the particles to repeatedly pass over the Sink-Hole, resulting in some sinking through the media, and others remaining on the mesh. By adjusting the mass of sand in the system and the superficial air velocity, it was possible to vary the separation density from 2.5 to 3.2 RD, whilst holding the Ep values in the range 0.1 to 0.2 RD.